STUDIES ON LIPOLYTIC BACTERIA IN STORED FISH ETROPLUS SURATENSIS (BLOCH) - SREEKUMARI, K R; CHANDRASEKHARAN, M; LAKSHMANAPERUMALSAMY, P (Fishery Technology, 2017)
The distribution of total hectrotrophic bacteria (THB) and lipolytic bacteria in various regions (body surface, gill, intestine and flesh) of fish Etroplus suratensis (Bloch) during storage at 28 + 2°C and 4 °C was studied. Pseudomonas dominated at reduced temperature whereas at 28 + 2°C and in fresh condition Vibrio, Aeromonas, and Acinetobacter dominated. Lipolytic activity was elaborated by the members of various genera and their activity varied in different lipid compounds 80, between 60, tween 40 and tween 20). Tributyrin was utilized by maJonty of the isolates. AH the selected isolates preferred a temperature of 35°C and pH 6.0 for their maximum growth. Aeromonas and Vibrio showed maximum growth at 0.5 % Na CJ concentration while 3 % NaCl was found to be optimum for Pseudomonas.